Germline mutations in young non-smoking women with lung adenocarcinoma. (August 2018) - Donner, Iikki; Katainen, Riku; Sipilä, Lauri J.; Aavikko, Mervi; Pukkala, Eero; Aaltonen, Lauri A.
Highlights: We utilized population-based sampling of the youngest never-smoker female patients. We found probable susceptibility variants in BRCA1, BRCA2, and TP53. Altogether 23 candidate predisposition genes for LUAD in women are reported. Abstract: Objectives: Although the primary cause of lung cancer is smoking, a considerable proportion of all lung cancers occur in never smokers. Gender influences the risk and characteristics of lung cancer and women are overrepresented among never smokers with the disease. Young age at onset and lack of established environmental risk factors suggest genetic predisposition. In this study, we used population-based sampling of young patients to discover candidate predisposition variants for lung adenocarcinoma in never-smoking women. Materials and methods: We employed archival normal tissue material from 21 never-smoker women who had been diagnosed with lung adenocarcinoma before the age of 45, and exome sequenced their germline DNA. Results and conclusion: Potentially pathogenic variants were found in eight Cancer Gene Census germline genes: BRCA1, BRCA2, ERCC4, EXT1, HNF1 A, PTCH1, SMARCB1 and TP53 . The variants in TP53, BRCA1, and BRCA2 are likely to have contributed to the early onset lung cancer in the respective patients (3/21 or 14%). This supports the notion that lung adenocarcinoma can be a component of certain cancer predisposition syndromes. Fifteen genes displayed potentially pathogenic mutations in at least two patients: ABCC10, ATP7B, CACNA1S, CFTR, CLIP4, COL6A1, COL6A6, GCN1, GJB6, RYR1, SCN7A, SEC24A, SP100, TTN and USH2A . Four patients showed a mutation in COL6A1, three in CLIP4 and two in the rest of the genes. Some of these candidate genes may explain a subset of female lung adenocarcinoma.